Composite positive electrode material and preparation method thereof, positive electrode, battery and battery application
By forming an ABO3 perovskite cladding on the surface of the lithium-rich positive electrode material, the reduction in battery circulation performance and gas production caused by oxygen release of lithium-rich positive electrode material is solved, and more stable battery performance is achieved.
Patent Information
- Application Number
- CN202310942632.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-28
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-07-28
AI Technical Summary
The existing lithium-rich cathode materials have poor phenomena such as reduced battery circulation performance and gas production due to oxygen release.
A composite positive electrode material is used, which consists of a lithium-rich positive electrode material as a core body, and an ABO3 perovskite coating is formed on its surface. A in ABO3 includes La, Sr, and B includes Fe, Ti, Mo, Ga, Ru, Zr, Ir, Co and other elements.
It significantly reduces the oxygen release phenomenon of lithium-rich positive electrode materials in the core body, improves the stability of the crystal structure, enhances the stability of the interface with the electrolyte, reduces gas production, and thus improves the circulation performance of the battery.
Smart Images

Figure CN119447199A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of battery technology, and specifically relates to a composite positive electrode material and a preparation method thereof, a positive electrode, a battery and battery applications. Background Art
[0002] Lithium-ion batteries have rapidly become popular in electric vehicles, 3C electronic products, energy storage devices, etc. due to their high energy density and low self-discharge. With the popularization of lithium batteries, the requirements for their electrochemical properties, such as cycle performance, are becoming higher and higher.
[0003] The positive electrode material of lithium-ion batteries has an important influence on the electrochemical performance of the battery. For example, lithium-rich positive electrode materials not only give the battery high energy density, but also have an important influence on the battery's cycle performance and safety performance. The oxygen on the surface of the lithium-rich positive electrode material easily escapes from the lattice position, which will cause the instability of its crystal skeleton, thereby causing the capacity of the lithium-rich positive electrode material to decay, resulting in reduced battery cycle performance. In addition, the escaped oxygen entering the electrolyte will also cause side reactions in the electrolyte, resulting in adverse phenomena such as gas production, thereby reducing the safety and other performance of the battery. Summary of the invention
[0004] In view of the above problems, the present application provides a composite positive electrode material and a preparation method thereof, a positive electrode and a battery to solve the technical problems of existing lithium-rich positive electrode materials such as reduced battery cycle performance and gas production due to oxygen release.
[0005] In a first aspect, an embodiment of the present application provides a composite positive electrode material. The composite positive electrode material of the present application comprises a core body and a coating layer covering the core body, wherein the core body contains a lithium-rich positive electrode material, and the coating layer contains ABO 3 Perovskite, wherein A includes at least one element of La and Sr, and B includes at least one element of Fe, Ti, Mo, Ga, Ru, Zr, Ir, and Co.
[0006] The core material in the embodiment of the present application includes a lithium-rich positive electrode material with a high gram capacity, and the coating layer contains a specific type of ABO 3 Perovskite can form an oxygen buffer layer, thereby significantly reducing the oxygen release phenomenon of lithium-rich positive electrode materials in the core, effectively alleviating the capacity decay of lithium-rich positive electrode materials, and improving the stability of the crystal structure of lithium-rich positive electrode materials, so as to significantly improve the cycle performance of composite positive electrode materials. 3 The chemical stability of the perovskite coating layer itself and its ability to reduce the amount of oxygen in the composite positive electrode material escaping into the electrolyte effectively improve the stability of the interface between the positive electrode containing the composite positive electrode material and the electrolyte and reduce the gas production of the positive electrode.
[0007] In some embodiments, the ABO3 Perovskite types include LaFeO 3 、LaTiO 3 、LaMoO 3 、LaGaO 3 、LaRuO 3 、SrTiO 3 、SrZrO 3 、LaIrO 3 、LaCoO 3 At least one of the above ABO 3 Perovskite as a coating material can improve the slow deoxidation effect of the coating layer and further improve the stability of the crystal structure of the lithium-rich positive electrode material, thereby further alleviating the capacity decay of the core body including the lithium-rich positive electrode material. 3 Perovskite can further improve the stability of its interface with the electrolyte.
[0008] In some embodiments, the ABO 3 The mass ratio of perovskite to core is (0.2-0.8):100, and can be optionally (0.25-0.7):100.
[0009] In some embodiments, the ABO 3 The total content of elements A and B in the perovskite in the composite positive electrode material is 800 to 5400 ppm, and can be optionally 1200 to 5000 ppm.
[0010] By placing ABO 3 The content of perovskite in the composite cathode material is controlled within this range, which can increase the ABO 3 The slow deoxygenation synergistic effect between the perovskite and the lithium-rich cathode material in the core can further improve the stability of the crystal structure of the lithium-rich cathode material, thereby significantly improving the cycle performance of the composite cathode material. 3 Perovskite can also effectively adjust the thickness of the coating layer and the stability of the contact interface with the electrode liquid, reducing the gas production of the positive electrode.
[0011] In some embodiments, the coating layer has a thickness of 0.05 to 1 μm, and may be 0.1 to 0.4 μm.
[0012] By controlling the thickness of the coating layer within this range, the ABO can be adjusted. 3 The content of perovskite in the composite positive electrode material can further increase the ABO 3 The slow deoxygenation synergistic effect between the perovskite and the lithium-rich cathode material in the core body improves the stability of the crystal structure of the lithium-rich cathode material and the stability of the contact interface with the electrode liquid. At the same time, it can also take into account the high gram capacity of the composite cathode material.
[0013] In some embodiments, the lithium-rich cathode material comprises a lithium-rich manganese-based cathode material, wherein the lithium-rich manganese-based cathode material is Li[Li x Ni a Co b Mn c M d ]O 2 , wherein x+a+b+c+d=1, x>0, a+b+c+d<1, 0<b<0.1, and M includes at least one of Mg, Nb, Cr, Ce, Fe, Ta, Al, V, Ti, Zr, Sn and Mo.
[0014] The lithium-rich manganese-based positive electrode material shown in the structural formula has a high gram capacity, which makes the composite positive electrode material have a high gram capacity, and is different from the above-mentioned ABO in the coating layer. 3 Perovskites can play a synergistic role in slowing down the oxygen release, further alleviating the oxygen release phenomenon of the composite positive electrode material, thereby further alleviating the capacity decay of the lithium-rich positive electrode material to improve its cycle performance.
[0015] In some embodiments, the Dv50 particle size of the core body is 5 to 11 μm, and can be optionally 6 to 8 μm.
[0016] The core body with a particle size in this range can not only increase the proportion of lithium-rich positive electrode materials in the composite positive electrode material, but also increase the gram capacity of the composite positive electrode material. Moreover, the particle size range of the core body and the thickness range of the above-mentioned coating layer make the particle size of the composite positive electrode material distributed in a certain range, thereby improving the properties of the composite positive electrode material, including compaction density. At the same time, the core body with a particle size in this range can match the content of perovskite in the lithium-rich positive electrode material with that in the coating layer of the above-mentioned thickness range, thereby improving the role of the oxygen buffer layer played by the coating layer on the basis of making the composite positive electrode material have a relatively high gram capacity, further inhibiting the oxygen release of the lithium-rich positive electrode material, thereby further alleviating the capacity decay of the lithium-rich positive electrode material, and further improving the cycle performance of the composite positive electrode material and the stability of the interface with the electrolyte.
[0017] In some embodiments, the characteristics of the composite cathode material include at least one of the following (1) to (4):
[0018] (1) The dislocation density is 1.55×10 11 ~3.5×10 11 m / m -3 , optional 1.8×10 11 ~3.2×10 11 m / m -3 ;
[0019] (2) Micro stress is 0.3-3.0%, and can be selected as 0.3-1.0%;
[0020] (3) Specific surface area BET is 1.2 to 2.5 m 2 / g, optional range is 1.35~2.3m 2 / g;
[0021] (4) The Dv50 particle size is 6.5 to 11 μm, and can be optionally 7 to 10.5 μm.
[0022] When the dislocation density of the double-checked positive electrode material is within the above range, the stacking faults can be relatively significantly reduced, thereby improving the voltage attenuation problem of the double-checked positive electrode material during the battery cycle and improving the voltage stability of the composite positive electrode material. When the microstress of the double-checked positive electrode material is within the above range, the stress accumulation phenomenon of the composite positive electrode material particles during the charge and discharge cycle can be significantly alleviated, thereby improving the stability of the particle structure of the composite positive electrode material. When the specific surface area of the double-checked positive electrode material is within the above range, the stability of the contact interface between the composite positive electrode material and the electrolyte can be relatively improved, and the side reactions of the contact interface can be reduced, thereby significantly improving the long-term performance of the composite positive electrode material including the cycle performance. When the Dv50 of the double-checked positive electrode material is within the above range, the compaction density and structural stability of the double-checked positive electrode material as well as other electrochemical properties including the first reversible capacity can be improved.
[0023] In a second aspect, the present invention provides a method for preparing a composite positive electrode material. The method for preparing a composite positive electrode material of the present invention comprises the following steps:
[0024] The positive electrode material particles are mixed with ABO 3 The perovskite precursors are mixed to obtain a mixture;
[0025] The mixture is sintered to form ABO-containing 3 A coating layer of perovskite is formed to obtain a composite positive electrode material;
[0026] Wherein, the positive electrode material particles contain lithium-rich manganese-based positive electrode materials, and the ABO 3 A includes at least one element of La and Sr, and B includes at least one element of Fe, Ti, Mo, Ga, Ru, Zr, Ir, and Co.
[0027] The preparation method of the composite positive electrode material in the embodiment of the present application adopts ABO 3 The perovskite precursor is used as a raw material to directly form ABO on the surface of the positive electrode material particles containing lithium-rich positive electrode materials. 3The coating layer of the perovskite is formed to generate the composite positive electrode material of the embodiment of the present application with a core-shell structure. In addition, the conditions for forming the coating layer on the surface of the positive electrode material particles in the preparation method of the composite positive electrode material of the embodiment of the present application are controllable, so that the prepared composite positive electrode material has stable performance and high efficiency, and is suitable for industrial large-scale production and application.
[0028] In some embodiments, the ABO 3 Perovskite precursors include LaFeO 3 、LaTiO 3 、LaMoO 3 、LaGaO 3 、LaRuO 3 、SrTiO 3 、SrZrO 3 、LaIrO 3 、LaCoO 3 At least one perovskite precursor.
[0029] By comparing the positive electrode material particles with ABO 3 The perovskite precursors are mixed in a ratio range to control the thickness of the generated coating layer to be within the range of 0.05 to 1 μm as described above. 3 The total content of A and B elements contained in the perovskite in the composite positive electrode material is controlled to be 1000-5000ppm. 3 The perovskite precursor is selected and controlled to enhance the role of the coating layer as an oxygen buffer layer, further reduce the oxygen release of the lithium-rich cathode material in the core and improve the stability of the interface between the composite cathode material and the electrolyte.
[0030] In some embodiments, the sintering process includes at least one of the following conditions (1) to (3):
[0031] (1) The sintering temperature is 500-750°C, and can be 500-650°C;
[0032] (2) heating the temperature to the sintering temperature at a heating rate of 2 to 5°C / min;
[0033] (3) When the sintering temperature is 500-650℃, the sintering time is 6-10h.
[0034] This range of sintering temperature enables ABO 3 The perovskite precursor is completely sintered and forms ABO 3 The coating layer of perovskite covers the positive electrode material particles. Controlling the heating rate within this range can effectively regulate the ABO 3 Perovskite crystals grow, so that the generated ABO 3The perovskite coating can more effectively act as an oxygen buffer layer, further reducing the oxygen release of the lithium-rich cathode material in the core and improving the stability of the interface between the composite cathode material and the electrolyte.
[0035] In a third aspect, the present application provides a positive electrode, which contains the composite positive electrode material of the above-mentioned embodiment of the present application or the composite positive electrode material prepared by the composite positive electrode material preparation method of the above-mentioned embodiment of the present application.
[0036] The positive electrode active layer of the embodiment of the present application contains the composite positive electrode material of the embodiment of the present application. Therefore, it not only has a high energy density, but also has good cycle performance, good stability of the interface in contact with the electrolyte, and can effectively reduce gas production.
[0037] In a fourth aspect, an embodiment of the present application provides a battery. The battery of the embodiment of the present application includes a positive electrode of the embodiment of the present application.
[0038] Since the battery of the embodiment of the present application contains the positive electrode of the embodiment of the present application, the battery of the embodiment of the present application has good cycle performance, low gas production and relatively high safety on the basis of electrochemical properties such as high energy density.
[0039] In a fifth aspect, the present application provides an electric device. The electric device of the present application includes a battery of the present application.
[0040] The electrical device in the embodiment of the present application has a long standby or battery life and is highly safe to use.
[0041] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:
[0043] Figure 1 A schematic diagram of the structure of a composite positive electrode material according to some embodiments of the present application;
[0044] Figure 2 A schematic diagram of the structure of the positive electrode of some embodiments of the present application;
[0045] Figure 3 Another schematic diagram of the structure of the positive electrode of some embodiments of the present application;
[0046] Figure 4 This is a schematic structural diagram of an implementation of a battery cell according to an embodiment of the present application;
[0047] Figure 5 for Figure 4 An exploded schematic diagram of the battery cell shown;
[0048] Figure 6 This is a schematic structural diagram of an implementation scheme of a battery module according to an embodiment of the present application;
[0049] Figure 7 This is a schematic structural diagram of an implementation scheme of a battery pack according to an embodiment of the present application;
[0050] Figure 8 for Figure 7 A schematic diagram of the exploded structure of the battery pack shown;
[0051] Fig. 9 A schematic diagram of an embodiment of an electrical device including a battery according to an embodiment of the present application as a power source;
[0052] The reference numerals in the specific implementation manner are as follows:
[0053] 10-composite positive electrode material, 11-core, 12-coating layer;
[0054] 20-positive electrode, 21-current collector, 22-active layer;
[0055] 30-battery cell, 31-housing, 32-electrode assembly, 33-cover plate;
[0056] 40-battery module;
[0057] 50-battery pack, 51-box, 52-lower box. DETAILED DESCRIPTION
[0058] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0059] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0060] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0061] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0062] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0063] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0064] In the description of the embodiments of the present application, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the embodiments of the present application.
[0065] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral one; it can be a mechanical connection or an electrical connection; it can be directly connected or indirectly connected through an intermediate medium, and it can be the internal connection of two elements or the interaction relationship between two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances. With the rapid popularization of the application of lithium batteries, especially in electric vehicles, the requirements for the cycle performance and safety of lithium batteries are becoming increasingly higher.
[0066] The positive electrode is one of the important components of the battery, which contains positive electrode active materials. The positive electrode active material has an important influence on the electrochemical performance of the battery, such as the battery's cycle performance, energy density and safety performance. With the emergence of lithium-rich positive electrode materials, the energy density of the battery has been significantly improved. However, lithium-rich positive electrode materials also have certain shortcomings. For example, the lithium-rich manganese-based positive electrode material in the lithium-rich positive electrode material has oxygen release phenomenon, which is specifically manifested as the oxygen on the surface of the lithium-rich positive electrode easily escapes from the lattice position, causing the instability of its crystal skeleton, thereby reducing the battery's cycle performance.
[0067] Moreover, the escaped oxygen is highly reactive and will reduce the stability of the interface between the electrode and the electrolyte. For example, it will corrode the electrolyte at the electrode / electrolyte interface, leading to unstable SEI and corresponding proton generation. The protons will continue to etch the material and accelerate these adverse reactions, such as gas production and other adverse phenomena.
[0068] In order to effectively alleviate the phenomenon of oxygen release from lithium-rich positive electrode materials and improve the stability of lithium-rich positive electrode materials, there are reports on constructing a coating layer on the surface of the lithium-rich positive electrode material to achieve coating modification of the lithium-rich positive electrode material. However, research has found that the oxygen release phenomenon of the currently disclosed lithium-rich positive electrode material with a coating structure has been improved to a certain extent compared to the lithium-rich positive electrode material without a coating layer, but it is still not ideal.
[0069] In order to further alleviate the oxygen release phenomenon of lithium-rich positive electrode materials and further improve the stability of the structure and electrochemical performance of lithium-rich positive electrode materials. Through research, the embodiment of the present application provides a composite positive electrode material with a coating structure, specifically using perovskite as a coating layer material, and selecting and controlling the type of perovskite material, etc., to improve the synergistic effect between the coating layer and the lithium-rich positive electrode material, and to improve the modification effect of the coating layer on the lithium-rich positive electrode material, which can significantly alleviate the oxygen release phenomenon of the lithium-rich positive electrode material and improve the crystal structure stability of the composite positive electrode material, thereby significantly improving the electrochemical performance of the battery including the cycle performance.
[0070] Composite cathode materials
[0071] In a first aspect, the present invention provides a composite positive electrode material. The composite positive electrode material of the present invention is a core-shell structure. In some embodiments, the structure of the composite positive electrode material of the present invention is as follows: Figure 1 As shown, the composite positive electrode material 10 includes a core 11 and a coating layer 12 covering the core 11. The core 11 contains a lithium-rich positive electrode material, and the coating layer 12 contains ABO 3 Perovskite, in which the ABO 3 A includes at least one element of La and Sr, and B includes at least one element of Fe, Ti, Mo, Ga, Ru, Zr, Ir, and Co.
[0072] The core-shell structure of the composite positive electrode material 10 in the embodiment of the present application refers to a core body 11 and a shell layer coating the core body 11, that is, a coating layer 12. Coating the core body 11 means that the coating layer 12 forms a film layer surrounding the surface of the core body 11. The core body 11 contains lithium-rich positive electrode materials. It can be understood that the materials of the core body 11 are all lithium-rich positive electrode materials. Of course, it can also contain other components on the basis of containing lithium-rich positive electrode materials, such as lithium-supplementing materials that are beneficial to increasing the capacity of lithium-rich positive electrode materials or additives that can synergistically work with the coating layer 12 to reduce the oxygen release of lithium-rich positive electrode materials. Similarly, the coating layer 12 contains ABO 3 Perovskite can be understood that the material of the coating layer 12 is all ABO 3 Perovskite, of course, can also contain ABO 3 The perovskite may also contain other components, such as ABO 3 Perovskite additives and other components play a synergistic role in alleviating oxygen release from lithium-rich positive electrode materials.
[0073] The core 11 contained in the composite positive electrode material 10 of the embodiment of the present application contains a lithium-rich positive electrode material, which gives the composite positive electrode material 10 a high gram capacity. 3 A and B in perovskite select specific elements, ABO 3 Perovskite has a relatively regular cubic perovskite structure with relatively high crystal symmetry. 2- The transport isotropy is relatively high, so this particular ABO 3Perovskite can form an oxygen buffer layer relatively better in the coating layer 12. Since the coating layer 12 can play a better role as an oxygen buffer layer, it can significantly inhibit the oxygen release phenomenon of the lithium-rich positive electrode material in the core 11, improve the stability of the crystal structure of the lithium-rich positive electrode material, and effectively alleviate the capacity decay of the lithium-rich positive electrode material, so as to significantly improve the cycle performance of the composite positive electrode material 10. Due to the oxygen slow release effect of the coating layer 12, the amount of oxygen in the composite positive electrode material 10 that escapes into the electrolyte can be effectively reduced; coupled with the above-mentioned types of ABO 3 The chemical properties of perovskite, such as acid resistance, are more stable than other perovskites, and the acid corrosion resistance is enhanced, such as being able to enhance the corrosion of HF, a side reaction product of the electrolyte. Therefore, through the combined effect of the oxygen slow release effect of the coating layer 12 and its own good chemical stability, the stability of the interface between the positive electrode containing the composite positive electrode material 10 and the electrolyte is effectively improved, and the gas generation phenomenon of the positive electrode is reduced.
[0074] In the embodiment, the lithium-rich positive electrode material contained in the core 11 of the composite positive electrode material 10 may include a lithium-rich manganese-based positive electrode material. The general molecular formula of the lithium-rich manganese-based positive electrode material can be expressed as Li[Li x Ni a Co b Mn c M d ]O 2 , wherein x+a+b+c+d=1, x>0, a+b+c+d<1, 0<b<0.1, and M includes at least one of Mg, Nb, Cr, Ce, Fe, Ta, Al, V, Ti, Zr, Sn and Mo. In the exemplary embodiment, the lithium-rich manganese-based positive electrode material may specifically include Li 1.2 Mn 0.48 Co 0.1 Ni 0.2 Ti 0.02 O 2 , Li 1.2 Mn 0.48 Co 0.1 Ni 0.2 Zr 0.02 O 2 , Li 1.2 Mn 0.48 Co 0.1 Ni 0.2 Mo 0.02 O 2 , Li 1.2 Mn 0.48 Co 0.1 Ni 0.2 V 0.02 O 2At least one of the above. The lithium-rich manganese-based positive electrode materials shown in these structural formulas have a high gram capacity, so that the composite positive electrode material 10 has a high gram capacity, and is different from the above-mentioned ABO in the coating layer 12. 3 The perovskites can play a synergistic role in slowing down the oxygen release, further alleviating the oxygen release phenomenon of the composite positive electrode material 10 and improving the cycle performance of the composite positive electrode material 10.
[0075] The core 11 in the composite positive electrode material 10 can be a regular morphology or an irregular morphology. For example, in the exemplary embodiment, the core 11 can be a spherical or spherical-like morphology, and of course, it can also be other morphologies. Moreover, its particle size and the thickness of the coating layer 12 can jointly affect the particle size of the composite positive electrode material 10. As in the embodiment, the Dv50 particle size of the core 11 can be 5 to 11 μm, and can be 6 to 8 μm. In the exemplary embodiment, it can be a typical but non-limiting particle size of 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, etc. Selecting and controlling the particle size of the core 11 within the above range can not only increase the content ratio of the lithium-rich positive electrode material in the composite positive electrode material 10, but also increase the gram capacity of the composite positive electrode material 10. Moreover, the core body 11 of this range of particle size can match the content of perovskite in the lithium-rich positive electrode material and the coating layer 12 relative to other particle size ranges, thereby improving the oxygen buffer layer role played by the coating layer 12 on the basis of making the composite positive electrode material 10 have a relatively high gram capacity, improving the inhibition of oxygen release from the lithium-rich positive electrode material, thereby further alleviating the capacity decay of the lithium-rich positive electrode material, and further improving the cycle performance of the composite positive electrode material 10 and the stability of the electrolyte interface. In addition, the particle size range of the core body 11 can also adjust the particle size of the composite positive electrode material 10 together with the coating layer 12, such as the Dv50 particle size of the composite positive electrode material 10 can be 6.5 to 11 μm, thereby improving the properties of the composite positive electrode material 10 including the compaction density.
[0076] In the embodiments, the coating layer 12 of the composite positive electrode material 10 in the above embodiments contains ABO 3 The mass ratio of perovskite to core 11 may be (0.2-0.8):100, or (0.25-0.7):100. In the exemplary embodiment, the mass ratio may be 0.2:100, 0.3:100, 0.4:100, 0.5:100, 0.6:100, 0.7:100, 0.8:100, etc., which are typical but non-limiting ratios. 3 The content of perovskite in the composite positive electrode material 10 is controlled within this range, which can increase the ABO 3 The slow deoxygenation synergistic effect between the perovskite and the lithium-rich positive electrode material in the core 11 can further improve the stability of the crystal structure of the lithium-rich positive electrode material in the core 11, thereby significantly improving the cycle performance of the composite positive electrode material 10.3 Perovskite can also effectively adjust the thickness of the coating layer 11 and the stability of the interface with the electrode liquid, thereby reducing the gas generation of the positive electrode.
[0077] In the embodiment, ABO 3 The total content of perovskite in the composite positive electrode material 10 is controlled to adjust the thickness range of the coating layer 12. As in the embodiment, the thickness of the coating layer 12 contained in the composite positive electrode material 10 can be controlled to be 0.05-1 μm, optionally 1-0.8 μm, and further can be 0.1-0.4 μm. In the exemplary embodiment, it can be 0.05-0.1 μm, 0.1-0.2 μm, 0.2-0.3 μm, 0.3-0.4 μm, 0.4-0.5 μm, 0.5-0.6 μm, 0.6-0.7 μm, 0.7-0.8 μm, 0.8-0.9 μm, 0.9-1 μm and other typical but non-limiting thickness ranges. By selecting the thickness of the coating layer 12 within this range, the ABO can be adjusted. 3 The content of perovskite in the composite positive electrode material 10 can increase ABO relative to other content ranges. 3 The slow deoxygenation synergistic effect between the perovskite and the lithium-rich positive electrode material in the core 11 and the stability of the crystal structure of the lithium-rich positive electrode material and the stability of the contact interface with the electrode liquid are improved. As shown in Table 2 below, the relevant performance of the batteries in Examples B1 to B4 is better than that of the batteries shown in Examples B5 and B6. At the same time, the high gram capacity of the composite positive electrode material 10 can also be taken into account. Among them, when the coating layer 12 contains only ABO 3 In the case of perovskite, the coating layer 12 of this thickness range is composed of ABO 3 The content of perovskite is regulated to form.
[0078] Based on the thickness of the coating layer 12 and the mass ratio range of the perovskite to the core body 11, it is detected that the coating layer 12 of the composite positive electrode material 10 of each embodiment contains ABO 3The total content of A and B elements in the perovskite in the composite positive electrode material 10 is 800-5400ppm1000-5000ppm, and can be 1200-5000ppm, 1500-4500ppm, and in the exemplary embodiment, it can be 1000-1500ppm, 1500-2000ppm, 2000-2500ppm, 2500-3000ppm, 3000-3500ppm, 3500-4000ppm, 4000-4500ppm, 4500-5000ppm, etc. Typical but non-limiting content ranges. Among them, the total content of A and B elements in the composite positive electrode material 10 can be determined by conventional methods of element content. As an example, ICP emission spectrometry (inductively coupled plasma emission spectrometer) can be used for determination, and the specific test process refers to the standard test method EPA 6010D-2014.
[0079] In the embodiment, the ABO contained in the coating layer 12 of the composite positive electrode material 10 of the above embodiments 3 The element types represented by A and B in perovskite, the valence of A ion can be +2 or +3, and the valence of B ion can be +3 or +4; the ionic radius r of the element represented by A A It can be 70pm≤r A ≤150pm; Ionic radius r of the element indicated by B B It can be 40pm≤r B ≤100pm, and r A >r B In this example, the ABO 3 Perovskite can specifically include LaFeO 3 、LaTiO 3 、LaMoO 3 、LaGaO 3 、LaRuO 3 、SrTiO 3 、SrZrO 3 、LaIrO 3 、LaCoO 3 At least one of the above ABO 3 Perovskite has higher O 2- The high transport isotropy and crystal symmetry can improve the role of the coating layer 12 as an oxygen buffer layer, thereby improving the slow deoxygenation effect of the coating layer 12, so as to further improve the stability of the crystal structure of the lithium-rich positive electrode material, thereby further alleviating the capacity decay of the lithium-rich positive electrode material, and significantly improving the cycle performance of the composite positive electrode material 10. 3Perovskite has stronger acid resistance, which further improves the stability of the interface between the positive electrode containing the composite positive electrode material 10 and the electrolyte and reduces the gas generation of the positive electrode.
[0080] Based on the core 11 and coating 12 contained in the above-mentioned composite positive electrode material 10, the dislocation density, microstress, specific surface area and particle size of the composite positive electrode material 10 can be improved by adjusting and controlling the particle size of the core 11 and the material and thickness of the coating 12, thereby further improving the mechanical properties of the composite positive electrode material 10 including structural strength and the electrochemical properties including voltage stability and stability of the contact interface with the electrolyte.
[0081] As shown in the embodiment, the dislocation density of the composite positive electrode material 10 in the above embodiments can be 1.55×10 11 ~3.5×10 11 m / m -3 , optional 1.8×10 11 ~3.2×10 11 m / m -3 , in this example, it can be 1.55×10 11 ~1.8×10 11 m / m -3 , 1.8×10 11 ~2.0×10 11 m / m -3 , 2.0×10 11 ~2.5×10 11 m / m -3 , 2.5×10 11 ~3.0×10 11 m / m -3 , 3.0×10 11 ~3.2×10 11 m / m -3 , 3.2×10 11 ~3.5×10 11 m / m -3 Typical but non-limiting dislocation density ranges are shown below. The dislocation density is a quantitative measure of the dislocations contained in the crystals of the composite positive electrode material 10, specifically the total length of the dislocation lines contained in the unit volume of the crystals. Controlling the dislocation density of the complex positive electrode material 10 within the above range can significantly reduce stacking faults relative to dislocation densities in other ranges, thereby significantly improving the voltage attenuation problem of the complex positive electrode material during battery cycling and relatively improving the voltage stability of the composite positive electrode material 10.
[0082] In the embodiments, the micro stress of the composite positive electrode material 10 of the above embodiments can be 0.3-3.0%, and can be 0.3-1.0%. In the exemplary embodiment, it can be 0.3-0.5%, 0.5-1%, 1-1.5%, 1.5-2%, 2-2.5%, 2.5-3%, etc. Typical but non-limiting micro stress ranges. Among them, micro stress refers to the stress acting between the microstructures of the composite positive electrode material 10, also known as micro residual stress, specifically refers to the stress existing between the grains or in the grains in the composite positive electrode material 10 due to factors such as deformation, phase change, and expansion of multiphase materials. The microstress of the composite positive electrode material is controlled within the above range. Compared with the microstress in other ranges, it can significantly improve the balance within the grains or between the grains in the composite positive electrode material 10, thereby significantly alleviating the stress accumulation phenomenon of the composite positive electrode material 10 particles during the charge and discharge cycle, thereby improving the stability of the particle structure of the composite positive electrode material 10 and significantly reducing the occurrence of secondary ball rupture caused by excessive stress in the composite positive electrode material 10.
[0083] In the embodiment, the BET specific surface area of the composite positive electrode material 10 in the above embodiments can be 1.2 to 2.5 m 2 / g, optional range is 1.35~2.3m 2 / g, in the example, it can be 1.2~1.35m 2 / g, 1.35~1.5m 2 / g, 1.5~1.8m 2 / g, 1.8~2m 2 / g, 2~2.3m 2 / g, 2.2~2.5m 2 / g and other typical but non-limiting specific surface area ranges. Among them, the BET specific surface area refers to the total area of the composite positive electrode material 10 per unit mass. The specific surface area of the composite positive electrode material is controlled within the above range. Compared with the specific surface area in other ranges, the contact area between the composite positive electrode material 10 particles and the electrolyte can be appropriate. On the basis of giving full play to the high gram capacity of the composite positive electrode material 10, the stability of the contact interface between the composite positive electrode material 10 and the electrolyte can be relatively improved, and the side reactions of the contact interface can be reduced, thereby significantly improving the long-term performance of the composite positive electrode material 10, including the cycle performance.
[0084] In the embodiments, the composite positive electrode material 10 of each embodiment can be controlled by the particle size of its core 11 and the thickness of the coating layer 12, and the Dv50 particle size of the composite positive electrode material 10 can be 6.5 to 11 μm, and can be 7 to 10.5 μm. In the exemplary embodiment, it can be a typical but non-limiting particle size range of 6.5 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, etc. The Dv50 particle size of the composite positive electrode material is controlled within the above range. Compared with the particle size in other ranges, the compaction density of the composite positive electrode material 10 particles can be improved and the structural stability of the composite positive electrode material 10 particles can be improved, and other electrochemical properties of the composite positive electrode material 10 including the first reversible capacity can be improved at the same time.
[0085] Preparation method of composite positive electrode material
[0086] In a second aspect, the present application embodiment provides a method for preparing the composite positive electrode material of the above-mentioned embodiment. The composite positive electrode material of the present application embodiment comprises the following steps:
[0087] Step S10: Mixing the positive electrode material particles with ABO 3 The perovskite precursors are mixed to obtain a mixture;
[0088] Step S20: Sintering the mixture to form ABO-containing 3 The coating layer of perovskite is used to obtain a composite positive electrode material.
[0089] Wherein, the positive electrode material particles in step S10 are as follows Figure 1 The core 11 contained in the composite positive electrode material 10 of the embodiment of the above application is shown, therefore, the positive electrode material particles in step S10 contain lithium-rich manganese-based positive electrode material. 3 The perovskite precursor is the ABO in the coating layer 12 contained in the composite positive electrode material 10 of the above-mentioned application embodiment. 3 Perovskite, specifically ABO 3 A in the formula includes at least one element selected from La and Sr, and B includes at least one element selected from Fe, Ti, Mo, Ga, Ru, Zr, Ir, and Co. Therefore, the coating layer formed on the surface of the positive electrode material particles in step S20 is as follows: Figure 1 The composite positive electrode material 10 of the above-mentioned embodiment of the present application includes a coating layer 12 .
[0090] Thus, the preparation method of the composite positive electrode material of the embodiment of the present application adopts ABO 3 The perovskite precursor is used as a raw material to directly form ABO on the surface of the positive electrode material particles containing lithium-rich positive electrode materials. 3The coating layer of perovskite is used to generate the composite positive electrode material 10 of the embodiment of the present application with a core-shell structure as described above. Therefore, the positive electrode material particles as the core body give the prepared composite positive electrode material high electrochemical properties including gram capacity. The formed coating layer effectively constitutes an oxygen buffer layer, which can inhibit the oxygen release phenomenon of the lithium-rich positive electrode material in the core body, thereby effectively improving the crystal structure stability of the lithium-rich positive electrode material in the core body, alleviating the capacity decay of the lithium-rich positive electrode material, and significantly improving the cycle performance of the composite positive electrode material. Moreover, the formed coating layer has stable chemical properties, effectively enhances the stability of the interface between the prepared composite positive electrode material and the electrolyte, and reduces the gas production phenomenon. In addition, the conditions for forming a coating layer on the surface of the positive electrode material particles in the preparation method of the composite positive electrode material in the embodiment of the present application are controllable, so that the prepared composite positive electrode material has stable performance and high efficiency, and is suitable for industrial large-scale production and application.
[0091] Step 10:
[0092] Since the positive electrode material particles in step 10 are Figure 1 The core 11 contained in the composite positive electrode material 10 of the embodiment of the present application is shown. Therefore, the components and particle size of the positive electrode material particles are the same as the components and particle size of the core 11 contained in the composite positive electrode material 10 above. Similarly, the ABO in step 10 3 The perovskite precursor is the ABO in the coating layer 12 contained in the composite positive electrode material 10 of the above-mentioned application embodiment. 3 The perovskite precursor of perovskite, therefore, ABO 3 The perovskite precursor can be specifically 3 The type of perovskite can be selected and controlled. Specifically, the ABO in the coating layer 12 of the composite positive electrode material 10 in the above application embodiment can be selected and controlled. 3 ABO corresponding to the selection of perovskite types 3 Perovskite precursors.
[0093] In addition, the positive electrode material particles can be prepared according to a conventional positive electrode material preparation method, or can be prepared according to a conventional positive electrode material preparation method with improvements. For example, in the exemplary embodiment, when the positive electrode material particles are lithium-rich positive electrode materials, specifically lithium-rich manganese-based material particles, they can be prepared according to a conventional lithium-rich positive electrode material, specifically a lithium-rich manganese-based material preparation method.
[0094] In the embodiment, the ABO 3 Perovskite precursors may include LaFeO 3 、LaTiO 3 、LaMoO 3 、LaGaO 3 、LaRuO 3 、SrTiO3 、SrZrO 3 、LaIrO 3 、LaCoO 3 At least one perovskite precursor is selected. These precursors can be sintered during the sintering process in step S30 to generate the corresponding ABO 3 Perovskite.
[0095] In the embodiment, the positive electrode material particles and ABO 3 The mixing process of the perovskite precursor can be a dry mixing process or a solution mixing process.
[0096] Among them, the dry mixing process can be to mix the positive electrode material particles with ABO 3 The powder of the perovskite precursor is directly mixed without solvent. In the embodiment, the dry mixing process can be to mix the positive electrode material particles with ABO 3 The mixture of perovskite precursors is directly subjected to stirring or ball milling.
[0097] The solution mixing process is relative to the above-mentioned dry mixing process. For example, in the embodiment, ABO 3 The perovskite precursor is prepared into a solution and mixed with the positive electrode material particles to form a mixture slurry, which is then dried to remove the solvent, so that the ABO 3 The perovskite precursor can form a precursor coating layer to coat the surface of the positive electrode material particles. 3 The perovskite precursor and the cathode material particles are mixed with a solvent to prepare a mixture slurry, which is then dried to remove the solvent, so that the ABO 3 The perovskite precursor can form a precursor coating layer to coat the surface of the positive electrode material particles.
[0098] In the mixing process of step S10, the positive electrode material particles and the ABO 3 The mixing ratio of the perovskite precursor is adjusted to adjust the mass content and thickness of the coating layer generated in step S20. 3 The mixing ratio of the perovskite precursor makes the positive electrode material particles and ABO 3 The mass ratio of the perovskite satisfies the ABO in the core 11 and the coating 12 of the composite positive electrode material 10 of the above-mentioned embodiment of the application. 3 The mass ratio of perovskite is 100:(0.2-0.8), and can be 100:(0.25-0.7). That is, in the embodiment, in step S10, the positive electrode material particles and ABO 3 The perovskite precursor is made by mixing the positive electrode material particles with ABO 3The mass ratio of perovskite is 100:(0.2-0.8), and can be 100:(0.25-0.7) for mixing. By controlling the two in this ratio range for mixing, the thickness of the coating layer generated in step S20 can be controlled within the above-mentioned range of 0.05-1 μm, and the generated ABO can also be 3 The total content of A and B elements contained in the perovskite in the composite positive electrode material is controlled to be 1000-5000 ppm, so as to enhance the function of the coating layer as an oxygen buffer layer, further reduce the oxygen release phenomenon of the lithium-rich positive electrode material in the core body, and improve the stability of the interface between the composite positive electrode material and the electrolyte.
[0099] Step 20:
[0100] During the sintering process in step 20, ABO 3 The perovskite precursor is sintered to generate the ABO in the coating layer 12 of the composite positive electrode material 10 of the above-mentioned application embodiment. 3 Perovskite, and can form ABO 3 The coating layer of perovskite covers the positive electrode material particles.
[0101] In the embodiment, the sintering temperature can be controlled to be 500-650°C. This temperature range can make ABO 3 The perovskite precursor is completely sintered and forms ABO 3 The coating layer of the perovskite coats the positive electrode material particles. At the sintering temperature, the sintering time should be sufficient, such as in the embodiment, when the sintering temperature is 500-650° C., the sintering time is 6-10 hours.
[0102] In the embodiment, the sintering process can be controlled to heat up to the sintering temperature at a heating rate of 2 to 5°C / min. By controlling the heating rate within this range, the ABO 3 Perovskite crystal growth, improving the generation of ABO 3 The perovskite coating acts as an oxygen buffer layer, further reducing the oxygen release of the lithium-rich cathode material in the core and improving the stability of the interface between the composite cathode material and the electrolyte.
[0103] positive electrode
[0104] In a third aspect, the embodiments of the present application provide a positive electrode. In some embodiments, Figure 2 and Figure 3 As shown, the positive electrode 20 of the present embodiment includes a current collector 21 and an active layer 22. The active layer 22 is combined with the current collector 21. In the positive electrode 20 of the present embodiment, the positive electrode active material contained in the active layer 22 includes the composite positive electrode material 10 of the present embodiment.
[0105] Since the positive electrode active material contained in the active layer 22 of the positive electrode 20 of the embodiment of the present application includes the composite positive electrode material 10 of the embodiment of the present application, the positive electrode 20 of the embodiment of the present application not only has a high energy density, but also has good cycle performance, and its contact interface with the electrolyte has good stability, which can effectively reduce gas production.
[0106] Among them, the current collector 21 contained in the positive electrode 20 of the embodiment of the present application refers to a structure or part for collecting current. In the embodiment, the current collector 21 contained in the positive electrode 20 of the embodiment of the present application includes but is not limited to a metal current collector, a carbon current collector, a conductive resin current collector, a composite current collector of metal and resin, etc., more specifically, copper, nickel, titanium, iron and their respective alloys, stainless steel, carbon fiber, carbon nanotubes (CNT), graphite, etc. In the embodiment, the current collector 21 can also be a dense film layer, or a film layer with a porous structure.
[0107] The active layer 22 contained in the positive electrode 20 of the embodiment of the present application refers to a film layer containing a positive electrode active material. In the embodiment, the active layer 22 contained in the positive electrode 20 of the embodiment of the present application is combined with the current collector 21 and can be stacked on the surface of the current collector 21. When the surface layer of the current collector 21 contains a porous structure or the current collector 21 itself is a porous structure, the active layer 22 can be at least partially embedded in the current collector 21.
[0108] In the embodiment, when the active layer 22 is stacked on the surface of the current collector 21, it can be combined with one surface of the current collector 21, such as Figure 2 When the current collector 21 has two opposite surfaces, that is, when it is a membrane structure, the active layer 22 can be combined with the two opposite surfaces of the current collector 21, such as Figure 3 shown.
[0109] In the embodiment, the active layer 22 contained in the positive electrode 20 of the embodiment of the present application includes not only the composite positive electrode material 10 of the embodiment of the present application, but also necessary components such as positive electrode active materials and other components. The other components may include a binder or may further contain a conductive agent, other additives and other components.
[0110] In the embodiment, when the active layer 22 contains a binder, the binder may include one or more of an oil-soluble binder, a water-soluble binder, an emulsion-type binder, etc. In an exemplary embodiment, the oil-soluble binder may include one or more of polyvinylidene fluoride, polyimide, polytetrafluoroethylene, polybutyl acrylate, polyacrylonitrile, etc.; in an exemplary embodiment, the water-soluble binder may include one or more of carboxymethyl cellulose, carboxymethyl cellulose salt, polyacrylic acid, polyacrylic acid salt, polyvinyl alcohol, sodium alginate, cyclodextrin, etc.; in an exemplary embodiment, the emulsion-type binder may include one or more of styrene-butadiene rubber, vinyl acetate resin, acrylic resin, and chlorinated rubber.
[0111] In an embodiment, when the active layer 22 contains a conductive agent, the conductive agent may include one or more of acetylene black (SP), carbon nanotubes, conductive carbon black (super-P), Ketjen black, carbon fiber, graphene, and the like.
[0112] In the embodiment, when the active layer 22 contains other additives, the additives may include but are not limited to functional components such as lithium supplements.
[0113] The above-mentioned positive electrode active material, binder, conductive agent and other materials can be selected according to the application or production requirements of the positive electrode 20.
[0114] The positive electrode 20 of the embodiment of the present application can be prepared according to a conventional positive electrode preparation method, such as including the following steps: preparing a slurry containing the above-mentioned composite positive electrode material and a binder and a solvent or further containing components such as a conductive agent and other additives, and forming a film (wet film) of the slurry on the current collector 21; then performing a drying process to evaporate the solvent, thereby drying the wet film; and then rolling the dried film layer to form an active layer 22, thereby obtaining the positive electrode 20.
[0115] Battery
[0116] In a fourth aspect, the present application also provides a battery. The battery of the present application comprises a positive electrode and a negative electrode, wherein the positive electrode is the positive electrode 20 of the present application.
[0117] Since the battery of the embodiment of the present application contains the positive electrode 20 of the embodiment of the present application, the battery of the embodiment of the present application has good cycle performance, low gas production and relatively high safety on the basis of electrochemical properties such as high energy density.
[0118] In the embodiment, the negative electrode contained in the battery of the embodiment of the present application can be a conventional negative electrode, such as in the embodiment, it can be a negative electrode that matches the positive electrode 20 of the embodiment of the present application.
[0119] Of course, the battery of the present application embodiment may include other necessary components or auxiliary components in addition to the above-mentioned electrodes. For example, when the battery of the present application embodiment is an ion battery, the battery of the present application embodiment includes components or parts such as a diaphragm and an electrolyte.
[0120] In the embodiments, the batteries of the above embodiments may include any one of a battery cell, a battery module, and a battery pack.
[0121] The battery cell refers to a battery housing and an electrode assembly (also called a bare cell) encapsulated in the battery housing. The shape of the battery cell is not particularly limited, and it can be cylindrical, square, or any other shape. In an exemplary embodiment, the battery cell can be as follows: Figure 4The battery cell 30 shown has a square structure.
[0122] In some embodiments, Figure 5 As shown, the outer packaging of the battery cell 30 may include a shell 31 and a cover plate 33. The shell 31 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 31 has an opening connected to the receiving cavity, and the cover plate 33 is used to cover the opening to close the receiving cavity. The positive electrode 20, the separator and the negative electrode contained in the battery cell 30 of the embodiment of the present application can form an electrode assembly 32 through a winding process and / or a lamination process. The electrode assembly 32 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 32. The number of electrode assemblies 32 contained in the battery cell 30 can be one or more, which can be adjusted according to actual needs.
[0123] In some embodiments, the preparation method of the battery cell 30 can assemble the positive electrode 20, the separator, the negative electrode and the electrolyte of the above-mentioned embodiment of the application to form the battery cell 30. As an example, the positive electrode 20, the separator and the negative electrode of the above-mentioned embodiment of the application can be formed into an electrode assembly 32 through a winding process or a lamination process, and the electrode assembly 32 is placed in an outer package, and the electrolyte is injected after drying, and the battery cell 30 is obtained through vacuum packaging, standing, forming, shaping and other processes. Since the battery cell 30 contains the positive electrode 20 of the above-mentioned embodiment of the application.
[0124] In the embodiment, when the battery of the embodiment of the present application is a battery module, the battery module refers to being assembled from the battery cells 30, that is, it can contain a plurality of the battery cells 30, and the specific number can be adjusted according to the application and capacity of the battery module.
[0125] In some embodiments, Figure 6 FIG. 4 is a schematic diagram of a battery module 40 as an example. Figure 6 As shown, in the battery module 40, the plurality of battery cells 30 may be arranged in sequence along the length direction of the battery module 40. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 30 may be fixed by fasteners.
[0126] Optionally, the battery module 40 may further include a housing having an accommodation space, and the plurality of battery cells 30 may be accommodated in the accommodation space.
[0127] A battery pack is composed of the above-mentioned battery cells 30, that is, it may contain multiple battery cells 30, wherein multiple battery cells 30 may be assembled into the above-mentioned battery module 40. The specific number of battery cells 30 or battery modules 40 contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0128] As in the embodiment, Figure 7 and Figure 8is a schematic diagram of an example battery pack 50. The battery pack 50 may include a battery box and a plurality of battery modules 40 disposed in the battery box. The battery box includes an upper box body 51 and a lower box body 52, wherein the upper box body 51 is used to cover the lower box body 52 and form a closed space for accommodating the battery modules 40. The plurality of battery modules 40 may be arranged in the battery box in any manner.
[0129] Electrical devices
[0130] In the fifth aspect, the embodiments of the present application also provide an electric device. The electric device in the embodiments of the present application includes a power supply unit or an energy storage unit, and of course may also include other auxiliary components or necessary components. Among them, the power supply unit or energy storage unit contains the battery of the above-mentioned embodiment of the text application. The battery contained in the power supply unit or energy storage unit may be one or more. When there are multiple batteries, multiple batteries can form a battery module or battery pack. Since the electric device in the embodiments of the present application contains the battery of the above-mentioned embodiment of the text application, the power supply unit or energy storage unit of the electric device in the embodiments of the present application has high energy density, good cycle performance, long service life, and high safety, and the electric device in the embodiments of the present application has a long standby or battery life time and high safety in use.
[0131] Fig. 9 Schematic diagram of an electric device as an example. The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the requirements of the electric device for high power and high energy density, a battery pack or a battery module may be used.
[0132] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a secondary battery may be used as a power source.
[0133] In the embodiment, when the electrical device includes an energy storage unit, the electrical device may be an energy storage device, and the energy storage device includes the energy storage unit, and of course may also include other auxiliary components or necessary components. Among them, the energy storage unit contains the battery of the above text application embodiment. The battery contained in the energy storage unit may be one or more. When there are multiple batteries, multiple batteries can form a battery module or battery pack. Since the energy storage device of the embodiment of the present application contains the battery of the above text application embodiment, the energy storage device has high energy storage density, good cycle performance, long service life, and high safety.
[0134] Example
[0135] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0136] 1. Composite positive electrode material and preparation method thereof
[0137] Example A1
[0138] The present embodiment provides a composite positive electrode material and a preparation method thereof. The composite positive electrode material of the present embodiment comprises lithium-rich manganese-based positive electrode material particles, and a coating layer of lithium-rich manganese-based positive electrode material particles is coated on the surface of the lithium-rich manganese-based positive electrode material particles, and the coating layer is LaFeO 3 Perovskite coating layer. The relevant parameters of the lithium-rich manganese-based positive electrode material particles and the coating layer are shown in 1 below.
[0139] The preparation method of the composite positive electrode material comprises the following steps:
[0140] S1. Preparation of lithium-rich manganese-based positive electrode material particles: According to the molecular formula Li 1.2 Mn 0.48 Co 0.1 Ni 0.2 Ti 0.02 O 2 The molar ratio of elements contained in the lithium-rich manganese-based positive electrode material is accurately weighed Li 2 CO 3 Lithium salt, MnSO 4 ·H 2 O manganese salt, CoSO 4 7H 2 OCobalt salt, TiO 2 Each precursor compound is mixed with ball milled zirconium beads in a drum ball mill mixer at a ratio of 60:1 to obtain a precursor mixture; the precursor mixture is sintered in a muffle furnace at a sintering temperature of 800°C, a heating rate of 2°C / min, a sintering time of 10h, and an air atmosphere; the sintered material is mechanically ground and vibrated to obtain a molecular formula Li 1.2 Mn 0.48 Co 0.1 Ni 0.2 Ti 0.02 O 2 Lithium-rich manganese-based positive electrode material particles;
[0141] S2. Preparation of perovskite coating on the surface of lithium-rich manganese-based positive electrode material particles:
[0142] The precursor material of the perovskite material LaCl 3 and Fe 2 O 3 The La:Fe element molar ratio is 1:1 and the mixture is put into a drum ball mill mixer for 10 hours of mixing. Then, the lithium-rich manganese-based positive electrode material particles obtained in step S1 are added into the drum ball mill mixer for another 10 hours of mixing. The total mass of the precursor material of the perovskite material and the lithium-rich manganese-based positive electrode material particles are calculated according to the ratio of the perovskite LaFeO 3 The obtained mixture is mixed with lithium-rich manganese-based positive electrode material particles in a ratio of 0.25:100 by mass; the obtained mixture is placed in a muffle furnace for secondary sintering, the sintering temperature is 700°C, the heating rate is 3°C / min, the sintering time is 9h, the sintering atmosphere is air, and the sintered material is subjected to mechanical grinding and vibration screening to obtain a perovskite-coated lithium-rich manganese-based composite positive electrode material.
[0143] Embodiment A2 to Embodiment A13
[0144] The present embodiments A2 to A13 provide a composite positive electrode material and a preparation method thereof. The structures of the composite positive electrode materials provided in embodiments A2 to A13 are the same as those in embodiment A1, and each composite positive electrode material has a core-shell structure, and each composite positive electrode material includes lithium-rich manganese-based positive electrode material particles (core body) and a coating layer coating the core body, and the coating layer is a perovskite-containing coating layer. The relevant parameters of the lithium-rich manganese-based positive electrode material particles and the coating layer are shown in 1 below.
[0145] The preparation methods of the composite positive electrode materials provided in Examples A2 to A13 refer to the preparation method of the composite positive electrode material in Example A1, wherein the types of precursor materials and secondary sintering conditions of the perovskite material in S2 of the preparation methods of the composite positive electrode materials in each of Examples A2 to A13 are respectively as shown in Table 1 below.
[0146] Comparative Example A1
[0147] This comparative example provides a lithium-rich positive electrode material and a preparation method thereof. Compared with the composite positive electrode material in Example A1, the lithium-rich positive electrode material in this comparative example does not contain a coating layer, that is, the lithium-rich positive electrode material in this comparative example is the lithium-rich manganese-based positive electrode material particle as the core in Example A1.
[0148] Comparative Example A2
[0149] This comparative example provides a composite positive electrode material and a preparation method thereof. The composite positive electrode material of this comparative example is different from the composite positive electrode material in Example A2 in that the perovskite LaFeO 3 Replaced with LaAlO 3, and the others remain unchanged. Among them, the relevant parameters of the lithium-rich manganese-based positive electrode material particles and the coating layer contained in the composite positive electrode material of this comparative example are shown in 1 below.
[0150] The preparation method of the composite positive electrode material comprises the following steps:
[0151] S1. Preparation of lithium-rich manganese-based positive electrode material particles: prepared according to the method in Example A2.
[0152] S2. Preparation of perovskite coating on the surface of lithium-rich manganese-based positive electrode material particles:
[0153] The precursor material of the perovskite material LaCl 3 and Al 2 O 3 The La:Al element molar ratio is 1:1 and the mixture is put into a drum ball mill mixer for 10 hours of mixing. Then, the lithium-rich manganese-based positive electrode material particles obtained in step S1 are added to the drum ball mill mixer for another 10 hours of mixing. The total mass of the precursor material of the perovskite material and the lithium-rich manganese-based positive electrode material particles are calculated according to the ratio of the perovskite LaAlO 3 The obtained mixture is mixed with lithium-rich manganese-based positive electrode material particles in a ratio of 0.4:100 by mass; the obtained mixture is placed in a muffle furnace for secondary sintering, the sintering temperature is 700°C, the heating rate is 3°C / min, the sintering time is 9h, the sintering atmosphere is air, and the sintered material is subjected to mechanical grinding and vibration screening to obtain a perovskite-coated lithium-rich manganese-based composite positive electrode material.
[0154] Comparative Example A3
[0155] This comparative example provides a composite positive electrode material and a preparation method thereof. The composite positive electrode material of this comparative example is different from the composite positive electrode material in Example A2 in that the perovskite LaFeO 3 Replaced with LaMnO 3 , and the others remain unchanged. Among them, the relevant parameters of the lithium-rich manganese-based positive electrode material particles and the coating layer contained in the composite positive electrode material of this comparative example are shown in 1 below.
[0156] The preparation method of the composite positive electrode material comprises the following steps:
[0157] S1. Preparation of lithium-rich manganese-based positive electrode material particles: prepared according to the method in Example A2.
[0158] S2. Preparation of perovskite coating on the surface of lithium-rich manganese-based positive electrode material particles:
[0159] The precursor material of the perovskite material LaCl 3 and Mn 2 O 3The La:Mn element molar ratio is 1:1 and the mixture is put into a drum ball mill mixer for mixing for 10 hours. Subsequently, the lithium-rich manganese-based positive electrode material particles obtained in the previous step S1 are added to the drum ball mill mixer for mixing again for 10 hours. The obtained mixture is put into a muffle furnace for secondary sintering. The sintering temperature is 700°C, the heating rate is 3°C / min, the sintering time is 9 hours, and the sintering atmosphere is air. The sintered material is mechanically ground and vibrated to obtain a perovskite-coated lithium-rich manganese-based composite positive electrode material.
[0160] 2. Positive electrode sheet and battery examples
[0161] Example B1
[0162] This embodiment provides a positive electrode sheet and a battery cell containing the positive electrode sheet. The battery cell of this embodiment includes an electrode assembly formed by a positive electrode sheet, a separator and a negative electrode sheet, and also includes an electrolyte. The positive electrode sheet contains the composite positive electrode material in embodiment A1.
[0163] Preparation of positive electrode sheet: put the composite positive electrode material in Example A1 into 5 stirring tanks for premixing for 30 minutes, then add the conductive agent acetylene black (SP) and the binder polyvinylidene fluoride (PVDF) for secondary dry material mixing for 30 minutes, then add the solvent N-methylpyrrolidone (NMP) and stir rapidly under vacuum conditions to form a slurry. Among them, the mass ratio of composite positive electrode material: acetylene black: polyvinylidene fluoride = 96:2:2, and the solid content of the slurry is 70% by weight; the slurry is evenly coated on both sides of an aluminum foil with a thickness of 12μm, and the coated electrode is taken out after drying in an oven at 100-130℃ for half an hour; the positive electrode active material loading of the electrode is 21.5mg / cm 2 The positive electrode sheet is taken out and subjected to roller cold pressing to obtain a positive electrode sheet.
[0164] Preparation of negative electrode sheet: The negative electrode active material artificial graphite, hard carbon, conductive agent acetylene black, binder styrene butadiene rubber (SBR), and thickener sodium carbon methyl cellulose (CMC) are fully stirred and mixed in a deionized water solvent system in a weight ratio of 90:5:2:2:1, and then coated on copper foil, dried, and cold pressed to obtain a negative electrode sheet.
[0165] Separator: A polyethylene porous polymer film with a thickness of 12 μm.
[0166] Electrolyte: 1 mol / L LiPF 6 / (the solvent is EC+EMC+DMC, the volume ratio is 1:1:1).
[0167] Battery cell: stack the positive electrode sheet, separator and negative electrode sheet in order, place the separator between the positive and negative electrode sheets to isolate them, and wind them to obtain a bare cell; place the bare cell in an outer package, inject the prepared basic electrolyte, and package it to obtain a full battery.
[0168] Example B2 to Example B13
[0169] Embodiments B2 to B13 provide a positive electrode sheet and a battery cell including the positive electrode sheet, respectively.
[0170] The positive electrode sheets provided in each of the embodiments B2 to B13 are different from the positive electrode sheets in Embodiment B1 in that the positive electrode material contained in the positive electrode sheet in Embodiment B2 is the composite positive electrode material in Embodiment A2, the positive electrode material contained in the positive electrode sheet in Embodiment B3 is the composite positive electrode material in Embodiment A3, and so on. The positive electrode material contained in the positive electrode sheet in Embodiment B13 is the composite positive electrode material in Embodiment A13, and the rest are the same as the positive electrode sheet in Embodiment B1.
[0171] Then the battery cells provided in each of the embodiments B2 to B13 are different from the battery cells in Embodiment B1 in that the positive electrode sheets contained in the battery cells in Embodiment B2 are the positive electrode sheets in Embodiment B2 of the present application, that is, the positive electrode materials in the positive electrode sheets contained in the battery cells in each embodiment are the composite positive electrode materials in Embodiment A2. Similarly, the positive electrode sheets contained in the battery cells in Embodiment B3 are the positive electrode sheets in Embodiment B3, and so on. The positive electrode sheets contained in the battery cells in Embodiment B13 are the positive electrode sheets in Embodiment B13, and the rest are the same as the battery cells in Embodiment B1.
[0172] The preparation methods of the positive electrode sheets and battery cells provided in each of the embodiments B2 to B13 of the present invention respectively replace the contained positive electrode materials with the composite positive electrode materials in the corresponding embodiments, and the other steps and preparation conditions are the same as the preparation steps and preparation conditions in Embodiment B1.
[0173] Comparative Examples B1 to B3
[0174] Each of the embodiments of Comparative Examples B1 to B3 provides a positive electrode sheet and a battery cell containing the positive electrode sheet.
[0175] The positive electrode sheets provided in each of the comparative examples B1 to B3 are different from the positive electrode sheets in Example B1 in that the positive electrode material contained in the positive electrode sheet in Example B1 is the lithium-rich positive electrode material in Example A1, the positive electrode material contained in the positive electrode sheet in Example B2 is the composite positive electrode material in Example A2, and the positive electrode material contained in the positive electrode sheet in Example B3 is the composite positive electrode material in Example A3, and the rest are the same as the positive electrode sheet in Example B1.
[0176] 3. Composite cathode material and battery cell related performance tests:
[0177] 3.1 Related performance testing of composite positive electrode materials:
[0178] The lithium-rich positive electrode materials provided in the above-mentioned Examples A1 to A13 and Comparative Examples A1 to A3 were respectively tested for the relevant parameters shown in Table 1 using the following methods.
[0179] The method for detecting the thickness of the coating layer contained in the composite positive electrode material is: using a transmission electron microscope (TEM) to scan a cross-sectional photograph of the coating layer, and then measuring the distance between the inner wall and the outer wall of the coating layer.
[0180] Detection method for Dv50 particle size of composite positive electrode materials and the core bodies contained therein: refer to GB / T 19077-2016 / ISO13320:2009 particle size distribution laser diffraction method, and use Malvern 3000 equipment for measurement.
[0181] Detection method of dislocation density of composite positive electrode materials: Based on XRD test β = (1 / D) 2 ×10 16 , where D = Kλ / Bcosθ, K = 0.9, λ = 1.5406, B is the half-height width of the crystal plane of the composite positive electrode material (hkl) in the XRD diffraction pattern, and θ is the diffraction angle.
[0182] Detection method of micro stress of composite positive electrode material: Micro stress = (βhkl × Cosθhkl) / (4sinθhkl), where θhkl is the diffraction angle of the crystal plane of the composite positive electrode material (hkl) in the XRD diffraction pattern, and βhkl is the half-height width of the crystal plane of the composite positive electrode material (hkl) in the XRD diffraction pattern.
[0183] Detection method of BET specific surface area of composite positive electrode material: refer to GB / T 19587-2004 gas adsorption BET method to measure the specific surface area of composite positive electrode material.
[0184] The results of the performance measurements of the composite cathode material and the battery cell are shown in Table 1 below:
[0185] Table 1
[0186]
[0187]
[0188] As can be seen from Table 1, the composite positive electrode material of the embodiment of the present application has a proper range of dislocation density, micro stress and specific surface area, so that the mechanical properties such as the strength of the composite positive electrode material particles of the embodiment of the present application are good, and the electrochemical properties such as the stability of the voltage stability and the contact interface with the electrolyte are improved. Moreover, the particle size can be adjusted by adjusting the core particle size and the coating layer thickness, such as adjusting the range in the above Table 1, so as to simultaneously improve the compaction density and other properties of the composite positive electrode material.
[0189] 3.2 Battery monomer related performance testing:
[0190] The battery cells provided in the above-mentioned Examples B1 to B13 and Comparative Examples B1 to B3 were subjected to relevant electrochemical performance tests as shown in Table 2 using the following methods, and the results were shown in Table 2 below.
[0191] Battery gas production detection method: discharge the battery cell to 2V at 0.1C and let it stand for 30 minutes, then fully charge it to 4.4V at 0.33C and let it stand for 30 days; test the initial volume of the battery cell and the volume after standing for 30 days by the water drainage method to obtain the volume expansion rate of the battery cell, volume expansion rate (%) = (volume after standing for 30 days / initial volume-1) × 100%.
[0192] Battery cell cycle retention rate (%): Take the whole battery cell as the test object, under a constant temperature environment of 25℃, at a voltage of 2.5V~4.45V, charge to 4.45V at a rate of 1C, then charge at a constant voltage at 4.45V to a current ≤0.05mA, let it stand for 5min, then discharge to 2.5V at a rate of 1C, record the discharge capacity, repeat the previous process, and obtain the capacity retention rate after the specified number of cycles, capacity retention rate = first cycle discharge capacity / discharge capacity at the specified number of cycles × 100%.
[0193] The detection method for determining the storage performance of a battery cell is as follows: at a constant temperature of 25°C, stand for 5 minutes, discharge to 2.5V at 1 / 3C, stand for 5 minutes, charge to 4.5V at 1 / 3C, then charge at a constant voltage at 4.5V to a current ≤0.05mA, stand for 5 minutes, the charging capacity at this time is recorded as C0, then discharge to 2.8V at 1 / 3C, the discharge capacity at this time is the initial gram capacity, recorded as D0; then charge the battery to 4.5V at a constant current of 0.33C and to a current ≤0.05mA at a constant voltage, stand for 5 minutes, and finally put it into a high and low temperature box at 60°C, stand for 1 hour, and store it after the battery temperature reaches the target temperature; take it out after 15 days, repeat the previous process at a constant temperature of 25°C, and record the capacity Dn (n=0,1,2……) every 15 days, and calculate the capacity retention rate after 60 days of storage: (D4-D0) / D0*100%.
[0194] Battery capacity test: In a constant temperature environment of 25℃, let it stand for 30 minutes, discharge to 2.3V at 0.33C, let it stand for 5 minutes, charge to 4.55V at 0.33C, then charge at constant voltage at 4.55V to a current ≤0.05mA, let it stand for 5 minutes, then discharge to 2.3V at 0.33C. The discharge capacity at this time is the initial gram capacity.
[0195] The relevant performance tests of battery cells are shown in Table 2 below:
[0196] Table 2
[0197]
[0198] It can be seen from the data in Table 2 that compared with the battery cells in comparative examples B1 to B3, the battery cells in embodiments B1 to B13 have relatively higher storage performance and cycle performance, relatively improved gram capacity, and relatively low gas production. Among them, relative to comparative example B1, the capacity retention rate of the battery in embodiment B5 is significantly improved, the gas production is significantly reduced, and the performance such as gram capacity is also improved. Therefore, on the basis of the same lithium-rich manganese-based positive electrode material particles, the addition of a perovskite-containing coating layer can alleviate the oxygen release phenomenon of the composite positive electrode material and improve the stability of the interface contact between the composite positive electrode material and the electrolyte. Relative to comparative examples B2 and B3, the capacity retention rate of the batteries in embodiments B2, B7 to B13 is also significantly improved, the gas production is significantly reduced, and the performance such as gram capacity is also improved. Therefore, on the basis of the same lithium-rich manganese-based positive electrode material particles and the same or similar coating thickness, the type of perovskite material in the coating layer contained in the composite positive electrode material of the embodiment of the present application is compared with LaAlO 3 、LaMnO 3 Such perovskites can significantly alleviate the oxygen release phenomenon of composite positive electrode materials and further improve the stability of the interface contact between the composite positive electrode materials and the electrolyte.
[0199] The coating layer contained in the composite positive electrode material of the embodiment of the present application. In Example B5, relative to Comparative Example B1, the capacity retention rate of the battery is significantly improved, the gas production is significantly reduced, and the performance such as gram capacity is also improved. Example B2, relative to Comparative Example B1, therefore, the composite positive electrode material of the embodiment of the present application significantly alleviates the oxygen release phenomenon of the lithium-rich positive electrode material contained therein by selecting and controlling the perovskite material contained in the coating layer, thereby improving the capacity stability and cycle performance of the composite positive electrode material.
[0200] Further comparison with Examples B1 to B6 shows that the battery cell related performance in Examples B1 to B4 is better than that in Examples B5 to B6. Therefore, on the basis that the perovskite material contained in the composite positive electrode material is the same, the thickness of the coating layer or the mass ratio of the perovskite material to the core body is further adjusted, and the effect of the coating layer including alleviating the oxygen release of the core positive electrode material can be further adjusted, such as controlling the coating layer to be in the range of 0.05 μm to 1 μm, further in the range of 0.1 μm to 0.4 μm or the mass ratio of the core body to the perovskite is 100:0.25 to 100:0.8. Compared with other content ranges, the oxygen release phenomenon of the lithium-rich positive electrode material contained in the composite positive electrode material is significantly alleviated, and the capacity stability and cycle performance of the composite positive electrode material are further improved.
[0201] Further comparing Examples B2 and B7 to B13, on the basis of the same or similar content of perovskite material contained in the composite positive electrode materials of each embodiment, changing the type of perovskite material can still alleviate the oxygen release phenomenon of the lithium-rich positive electrode material contained in the composite positive electrode material, thereby improving the capacity stability and cycle performance of the composite positive electrode material.
[0202] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A composite positive electrode material, comprising a core body and a coating layer coating the core body, characterized in that: The core contains a lithium-rich positive electrode material, and the coating layer contains ABO3 perovskite, wherein A includes at least one element of La and Sr, and B includes at least one element of Fe, Ti, Mo, Ga, Ru, Zr, Ir, and Co.
2. The composite positive electrode material according to claim 1, characterized in that: The ABO3 perovskite includes at least one of LaFeO3, LaTiO3, LaMoO3, LaGaO3, LaRuO3, SrTiO3, SrZrO3, LaIrO3, and LaCoO3.
3. The composite positive electrode material according to claim 1 or 2, characterized in that: The total content of the A and B elements in the ABO3 perovskite in the composite positive electrode material is 800 to 5400 ppm, and can be optionally 1200 to 5000 ppm; and / or The mass ratio of the ABO3 perovskite to the core body is (0.2-0.8):100, and can be optionally (0.25-0.7):
100.
4. The composite positive electrode material according to any one of claims 1 to 3, characterized in that: The lithium-rich positive electrode material comprises a lithium-rich manganese-based positive electrode material, wherein the lithium-rich manganese-based positive electrode material is Li[Li x Ni a Co b Mn c M d ]O2, wherein x+a+b+c+d=1, x>0, a+b+c+d<1, 0<b<0.1, and M includes at least one of Mg, Nb, Cr, Ce, Fe, Ta, Al, V, Ti, Zr, Sn and Mo.
5. The composite positive electrode material according to any one of claims 1 to 4, characterized in that: The Dv50 particle size of the core body is 5 to 11 μm, and can be optionally 6 to 8 μm.
6. The composite positive electrode material according to claim 1, characterized in that: The characteristics of the composite positive electrode material include at least one of the following (1) to (4): (1) The dislocation density is 1.55×10 11 ~3.5×10 11 m / m -3 , optional 1.8×10 11 ~3.2×10 11 m / m -3 ; (2) Micro stress is 0.3-3.0%, and can be selected as 0.3-1.0%; (3) Specific surface area BET is 1.2 to 2.5 m 2 / g, optional range is 1.35~2.3m 2 / g; (4) The Dv50 particle size is 6.5 to 11 μm, and can be optionally 7 to 10.5 μm.
7. A method for preparing a lithium-rich positive electrode material, characterized in that: The steps include: The positive electrode material particles are mixed with the ABO3 perovskite precursor to obtain a mixture; The mixture is sintered to form a coating layer containing ABO3 perovskite on the surface of the positive electrode material particles to obtain a lithium-rich positive electrode material; The positive electrode material particles contain lithium-rich manganese-based positive electrode materials, A in the ABO3 includes at least one element of La and Sr, and B includes at least one element of Fe, Ti, Mo, Ga, Ru, Zr, Ir, and Co.
8. The preparation method according to claim 7, characterized in that: The ABO3 perovskite precursor includes at least one perovskite precursor of LaFeO3, LaTiO3, LaMoO3, LaGaO3, LaRuO3, SrTiO3, SrZrO3, LaIrO3, and LaCoO3.
9. The preparation method according to claim 7 or 8, characterized in that: The sintering process includes at least one of the following conditions (1) to (3): (1) The sintering temperature is 500-750°C, and can be 500-650°C; (2) heating the temperature to the sintering temperature at a heating rate of 2 to 5°C / min; (3) When the sintering temperature is 500-650°C, the sintering time is 6-10 hours.
10. A positive electrode, characterized in that: A composite positive electrode material comprising the composite positive electrode material according to any one of claims 1 to 6 or a composite positive electrode material prepared by the preparation method according to any one of claims 7 to 9.
11. A battery, characterized in that: Comprising the positive electrode as claimed in claim 10.
12. An electrical device, characterized in that: Comprising the battery of claim 11.
Citation Information
Patent Citations
Lithium-rich antiperovskite-coated LCO-based lithium composite, method for preparing same, and positive electrode active material and lithium secondary battery comprising same
CN109155411A
A method for coating a perovskite structural material on that surface of a positive electrode particle
CN109244438A
Perovskite type oxygen vacancy compound modified lithium-rich manganese-based positive electrode material as well as preparation method and application thereof
CN112909256A
Lithium-rich nickel-containing ternary composite material as well as preparation method and application thereof
CN115304107A
Positive electrode material and preparation method thereof, positive electrode plate and secondary battery
CN116404161A